The Effect of Noise and Reverberation on Spatial Perception in Sequential Bilateral Cochlear Implant Users. - Kara, Halide Çetin; Kara, Eyyup; Ataş, Ahmet (Journal of the American Academy of Audiology, 2023)
Background Spatial orientation is an executive function which includes vital activities and auditory organization according to daily bodily movements, directionality, and environmental information. It is directly linked to the vision and hearing and used throughout life, building complex relationships with these systems, based on learning. Purpose Our purpose in our study is to try to see the effects of noise and reverberation on the users by comparing the localization and auditory performances of the cochlear implant (CI) user individuals in a silent, noisy environment and reverberation. Research Design All subjects were subjected to immitancemetric/audiological tests, language development test (TIFALDI, Receptive/Expressive Language Test score 7 years and above), localization determination in noise, and localization determination test in reverberation. Studysample : In our study, 18 female and 16 male bilateral CI users with profound sensorineural hearing loss were included. The age range of subjects was 8 years 4 months and 10 years 11 months. Data Collection and Analysis Data from subjects were collected prospectively. Data analysis was analyzed with SPSS 21 program. Results It was observed that the subjects did not have difficulty in determining the direction in silent condition, but they had a significant difficulty in localizing the 135-, 225-, and 315-degree angles especially when the noise was signal-to-noise ratio (SNR) –10 dB and the reverberation was 06 and 09 second (p ≤ 0.005). Subjects' performances were significantly altered in sequential implanted users both when the SNR was changed and in the presence of reverberation (p < 0.05). Conclusion As a result of our study, it is thought that individuals with hearing loss will experience intense difficulties, especially in noisy and reverberant environments such as schools, and using assistive listening devices in these environmental conditions will contribute positively to their academic development.